2020
DOI: 10.1111/oik.06780
|View full text |Cite
|
Sign up to set email alerts
|

The overlooked role of taphonomy in ecology: post‐mortem processes can outweigh recruitment effects on community functions

Abstract: Biogenic structures that persist post‐mortem are ubiquitous, but rarely considered as key ecological features. Post‐mortem structures in many ecological systems exert community‐level effects and thus the dynamics of their degradation (i.e. taphonomy) become important in affecting community functions and ecosystem services, and these often‐overlooked effects may rival the influence of recruitment and typical post‐recruitment processes. Moreover, in some highly researched habitat types, post‐mortem structures ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 90 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Similar effects were observed on invertebrate species richness and Shannon diversity, but these lacked statistical significance, possibly due to the low sample size, and thus low power, of this experiment. Other intertidal biogenic species have been found to maintain their facilitative ability beyond the point of death, though sometimes the identity of species associated with the biogenic habitat changes (Liversage et al, 2020; McAfee & Bishop, 2019; Uyà et al, 2020). Empty barnacle tests form important microhabitats for intertidal organisms (Barnes, 2000) and may thus continue to facilitate communities of organisms adapted to empty tests after barnacle death.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects were observed on invertebrate species richness and Shannon diversity, but these lacked statistical significance, possibly due to the low sample size, and thus low power, of this experiment. Other intertidal biogenic species have been found to maintain their facilitative ability beyond the point of death, though sometimes the identity of species associated with the biogenic habitat changes (Liversage et al, 2020; McAfee & Bishop, 2019; Uyà et al, 2020). Empty barnacle tests form important microhabitats for intertidal organisms (Barnes, 2000) and may thus continue to facilitate communities of organisms adapted to empty tests after barnacle death.…”
Section: Discussionmentioning
confidence: 99%
“…Foundation species (Dayton 1971) create complex biogenic habitat, which can provide thermally benign microhabitats for associated organisms, primarily through shading and moisture retention (Hesketh et al 2021, Lee et al 2021, Jurgens et al 2022, Christiansen et al 2022, Gutiérrez et al 2023. While the loss of foundation species often negatively impacts associated species (Ellison 2019), habitat formers may act as important facilitators even in death, leaving behind structures that can bolster recruitment (Liversage et al, 2020) and provide thermal refugia for motile organisms (Uyà et al 2020, Hesketh andHarley 2023). The importance of such facultative facilitations for bolstering organism survival and performance may increase with environmental stress, though there may be an upper limit beyond which stress cannot be effectively buffered (Bruno et al 2003, He et al 2013, Bulleri et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dead shells also offer another less studied opportunity, the potential to back track recent changes in the spatial distribution of oyster beds. Applications of dead assemblages of organisms in investigations of ecological changes have been scarce, but these studies have demonstrated that the distribution of dead organisms can function as a long-term record of changes in community structure and function (Liversage et al, 2020). For example, Kidwell (2007Kidwell ( , 2008 investigated community changes in response to anthropogenic activities (e.g., fishing) using dead assemblages.…”
Section: Introductionmentioning
confidence: 99%